Hydrodynamics in the tidal flat in semi-enclosed Xiangshan Bay - Li, Li; Xu, Jiayang; Kong, Gaoqiang; Li, Peiliang; Ren, Yihan; Wang, Huiqun (Frontiers in Marine Science, 2023)
Tidal flats provide a foundation for biological diversity and marine economy. Xiangshan Bay is a semi-enclosed bay that shelters large areas of tidal flats, and is known for its aquaculture. In this study, field trips were conducted in late autumn to measure the water level, current, water temperature, tidal flat temperature, and turbidity data of the tidal flat in the bay during Typhoon Lingling. The field data were well calibrated and used to investigate the hydrodynamics, temperature, and turbidity of the tidal flat. The results showed that the spring-neap tidal cycles at the sea surface level were well captured at both stations. The maximum tidal range was 5.5 m and 1.5 m during spring and neap tides, respectively. The tidal flat was occasionally exposed to air occasionally (30 min). The current velocity (<0.2 m/s) and waves (<0.15 m) at the field stations were weak, and the direction of flow was controlled by the geomorphology, even during Typhoon Lingling. Water was more turbid at station S2 (<0.8 kg/m3) than at station S1 (<0.2 kg/m3). The sea water temperature and tidal flat temperature were affected by tidal cycles, with larger variations occurring during spring tides than during neap tides. The maximum value of seawater temperature at S1 station was greater than that at station S2 during spring tides. The intrinsic mode functions (IMFs) of sea water temperature and surface tidal flat temperature were similar, as they are both subject to sea-air-tidal flat interactions. The IMFs of the middle and bottom layers in the tidal flat were less correlated. Temperature fluctuations in seawater and tidal flats were mainly affected by air temperature and tides. Small-scale features (>0.5 Hz) were important for water and tidal flat temperatures, particularly during typhoons. These findings provide field data for future studies on eco-hydrology and coastal engineering in tidal flats.